Nanocellulose-Based Film-Forming Hydrogels for Improved Outcomes in Atopic Skin - Katarina Bolko Seljak; Barbara Sterle Zorec; Mirjam Gosenca Matjaž (MDPI AG, 2023)
Atopic dermatitis (AD) is a chronic inflammatory skin disease characterized by impaired skin barrier function. Amongst the various dermal formulations that are being used and/or investigated for AD treatment, one of the advanced approaches is the use of hydrogels as film-forming systems that are applied directly to the skin and have the added value of providing a physical barrier, which is lacking in atopic skin. Novel film-forming hydrogels based on two different nanocrystalline celluloses (NCCs) in combination with one of two natural polymers (alginate or pectin) were developed for incorporation of betamethasone dipropionate (BDP). Initially, the low water solubility of BDP was resolved by prior dissolution in a self-microemulsifying drug delivery system (SMEDDS). The mixture of Kolliphor® EL/Capryol® 90 in a ratio of 8/2 was chosen on the merit of its high BDP-saturated solubility and no BDP precipitation upon water dilution, enabling BDP to remain dissolved after incorporation into hydrogels. The solvent evaporation method was used to prepare the films, and their high water retention capacity was confirmed in vitro on artificial membranes and pig ear skin. The presented results thus confirm NCC-based film-forming hydrogels as a very promising drug delivery system for AD treatment.